PENGARUH KEMANDIRIAN BELAJAR DAN SARANA PERPUSTAKAAN SEKOLAH TERHADAP HASIL BELAJAR PRAKTEK PENGANTAR EKONOMI DAN BISNIS DI SMK NEGERI 10 SURABAYA - Widodo, Slamet (UNIVERSITAS NEGERI SURABAYA, 2016)
This study aims to assess the effect of independent learning and school library facilities on learning outcomes practice on introductory economics and business subjects.This study uses a quantitative approach, with as many as 204 respondents were taken from the part of the population that has been determined, amounting to 418 students. Data were obtained through a questionnaire enclosed means party members who completed questionnaires answers through alternative answers that have been provided by the researcher.The data of this study focuses on a class XI student of Business and Management Expertise consisting of eleven classes that include skills programs Accounting, Office Administration, Banking and Retail Business Management which is exactly the lesson introductory class on economics and bisnsi given.Related to the objective (1), the results showed that there is influence of the independent learning Learning Outcomes Practice Introduction to Economics and Business Class XI at SMK Negeri 10 Surabaya. (2) the results showed that there is influence means the school library to learn the results of introductory economics and business practice in class XI in SMK Negeri 10 Surabaya. (3) The results showed that there is influence of independent learning and school library facilities simultaneously on learning outcomes of introductory economics and business practices